Insufficiency of an Aortic Valve Prosthesis due to Tissue Ingrowth: A Case Report - Christiansen, Stefan; Fehske, Wolfgang; Autschbach, Rüdiger (The Heart Surgery Forum, 2007)
Tissue ingrowth of a prosthetic heart valve usually leads to a stenosis. We report a rare case of a patient with a fixation of the prosthetic leaflet due to tissue ingrowth. This state caused a total prosthetic insufficiency. The therapy used to treat this prosthetic heart valve with tissue ingrowth is discussed in this report.